PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MOTOR SECOND PADA CV MAULANA MOTOR DEALER PUSAT KOTA TANGERANG SELATAN - Muhammad Firman Syah Muhammad Firman Syah; Arief Budiyanto (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This research aims to determine the effect of product quality and consumer trust on the decision to purchase secondhand motorcycles at CV Maulana Motor Central Dealer in South Tangerang City, both partially and simultaneously. The research method used is an associative quantitative method. The population in this research is consumers of CV Maulana Motor Central Dealer in South Tangerang City with a total of 96 respondents. Primary data was collected through questionnaires and processed using SPSS Version 27. The results showed that the variables of product quality (X1) and consumer trust (X2) had a positive and significant effect on purchase decisions (Y), both partially and simultaneously. The multiple regression equation obtained is Y=20.596+0.191X1+0.764X2. The correlation coefficient (r) value of 0.637 indicates a strong relationship between the independent variables and the dependent variable. The coefficient of determination (R²) value of 0.393 indicates that 39.3% of the variation in purchase decision can be explained by product quality and consumer trust, while the remaining 60.7% is influenced by other variables not included in the research model. Based on the simultaneous test results, the F count value was > F table or (31.808 > 3.09) with sig < 0.05, so it was concluded that there was a positive and significant simultaneous effect between product quality and consumer trust on the decision to purchase a secondhand motorcycle at CV Maulana Motor Central Dealer in South Tangerang City. Keywords: Product Quality; Consumer Trust; Purchase Decision.